Sensitized Fluorescence Organic Light-Emitting Diodes with Reduced Efficiency Roll-off - Zhiyi Li (Georg Thieme Verlag, 2021)
Thermally activated delayed fluorescence (TADF) sensitized fluorescence is a promising strategy to maintain the advantage of TADF materials and fluorescent materials. Nevertheless, the delayed lifetime of TADF sensitizer is still relatively long, which cause heavy efficiency roll-off. Here we reported a valid tactic to construct fluorescent devices with low efficiency roll-off by utilizing the TADF sensitizer with reduced delayed lifetime. By construct the sensitization system, the energy transfer efficiency can up to 90%. The high energy transfer efficiency and the TADF’s short delayed lifetime result in the high sensitization over 95%, maximum external quantum efficiency of 16.2%. Meanwhile the TADF sensitized-fluorescent devices exhibit reduced efficiency roll-off with a “onset” current density of 23 mA cm-2. Our results provide an effective strategy to reduce the efficiency roll-off of TADF sensitization system.